Pengaruh Ukuran Pemerintah Daerah, Opini Audit, Dan Leverage Terhadap Audit Delay - Maidelfian Putra Bakar; Fefri Indra Arza (Jurnal Eksplorasi Akuntansi, 2019)
Local governments are obliged to ensure that their financial statements are presented in a timely manner as they are a form of accountability to the public. These financial reports can be used by the public to evaluate the capabilities of local governments in managing their resources effectively and efficiently. Financial statements that were not provided on time may cause those report loses their capacity to influence decisions. The study was categorized into causative research. Where this study aims to see how far the independent variables affect the dependent variable. This research tries to explain the influence of local government size (X1), audit opinion (X2) and leverage (X3) as independent variable to audit delay (Y) as dependent variable. The population observed in this study is from regencies and cities in West Sumatera in 2015 and 2017. The result of this study shows that the audit opinion variable cause significant negative effect on audit delay. The local government size and the leverage variable doesn't affect audit delay. This study also shows that local government size, audit opinion, and leverage together influence audit delay